Faye the always angel Si Faye, ang palagi na lang anghel - Abad, Heidi Emily Eusebio (Lampara books, 2013)
When Faye was born, everyone in the family said she looked like an angel. She played the role of an angel in school plays nursery, kindergarten, and prep school. Now, in grade school, she is still an angel! She does not want to play the role anymore. Find out in this story what it takes to play the role of an angel and what it really means to be a real angel.